2008
DOI: 10.1620/tjem.216.165
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nuclear Expression of Growth Hormone Receptor in Uterine Cervical Neoplasms of Women under 40 Years Old

Abstract: There has been an increased incidence of cervical cancer among young women, and they tend to have a poor prognosis due to unknown reasons. We hypothesize growth hormone (GH) receptor (GHR) may be involved in the proliferation of cervical carcinoma, because GH-related neoplasms arise in various organs and the amount of GH secretion may be different according to age. GHR is normally expressed in the cell membrane and cytoplasm, while the nuclear distribution of GHR has been considered to reflect high proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Tissue immunohistochemistry reveals that the nuclear GHR is present in many proliferating cells, including a variety of cancers, such as breast cancer [92], colorectal carcinoma [93], hepatocellular carcinoma [94], melanoma [70] and uterine cervical neoplasms [95]. The translocation of a transmembrane receptor into the nucleus is known to occur for the EGFR, the FGF receptor and IFN-g receptor [96], and is often associated with cell transformation.…”
Section: Nuclear Ghr and Cancermentioning
confidence: 99%
“…Tissue immunohistochemistry reveals that the nuclear GHR is present in many proliferating cells, including a variety of cancers, such as breast cancer [92], colorectal carcinoma [93], hepatocellular carcinoma [94], melanoma [70] and uterine cervical neoplasms [95]. The translocation of a transmembrane receptor into the nucleus is known to occur for the EGFR, the FGF receptor and IFN-g receptor [96], and is often associated with cell transformation.…”
Section: Nuclear Ghr and Cancermentioning
confidence: 99%
“…Indeed, the progression of uterine cervical carcinoma in women has also been correlated with the appearance of the GHR in the nucleus of cancerous cells [279], and nuclear GHR expression is similarly a marker of tumorigenesis in other cancerous cells [241,280]. Nuclear targeting of the GH receptor is thought to induce cell proliferation, a dysregulated proliferative arrest and an induction of cell cycle progression, through increased expression of the proliferation-related proteins Survivin and Mybbp [280].…”
Section: Gh In Cancersmentioning
confidence: 99%
“…[9] GH have shown a potential carcinogenic role in colorectal cancer,[10] primary Ki-1 lymphoma of the skin,[11] liposarcoma and lipoma,[12] hepatocarcinoma,[13] breast cancer,[14] prostate cancer[15] and uterine cervical cancer. [16] The trials regarding the usefulness of GH in IBD have not reported an increased incidence of cancer.…”
Section: Growth Hormonementioning
confidence: 99%